EZH2 is involved in psoriasis progression by impairing miR-125a-5p inhibition of SFMBT1 and leading to inhibition of the TGFβ/SMAD pathway - Shengming Qu; Zhe Liu; Bing Wang (SAGE Publishing, 2021)
Aims: In this study, we aimed to decipher the impact of enhancer of zeste homolog 2 (EZH2) in psoriasis as well as the underlying mechanism. Methods: A mouse model of psoriasis was developed by means of imiquimod induction, with the expression of EZH2, microRNA-125a-5p (miR-125a-5p), and SFMBT1 determined. The role of EZH2, miR-125a-5p, and SFMBT1 in malignant phenotypes of HaCaT cells and the development of psoriasis in vivo was subsequently investigated through gain- and loss-of-function experiments. Chromatin immunoprecipitation assay and dual-luciferase reporter assay were conducted to explore the relationship between EZH2 or SFMBT1 and miR-125a-5p. Finally, the effects of EZH2 and miR-125a-5p on the transforming growth factor β (TGFβ)/SMAD pathway were analyzed. Results: Overexpressed SFMBT1 and EZH2 was detected while miR-125a-5p were downregulated in psoriasis tissues and human keratinocyte (HaCaT) cells. EZH2 increased the levels of IL-17A-induced cytokines and promoted the malignant phenotypes of HaCaT cells. Functionally, EZH2 reduced miR-125a-5p expression while miR-125a-5p targeted SFMBT1 to activate the TGFβ/SMAD pathway in vitro . Knockdown of EZH2 or up-regulation of miR-125a-5p inhibited cell proliferation and the levels of IL-17A-induced cytokines, but increased the expression of TGFβ1 and the extent of smad2 and smad3 phosphorylation in HaCaT cells. Notably, EZH2 contributed to the development of psoriasis in vivo by inhibiting the TGFβ/SMAD pathway via impairment of miR-125a-5p-mediated SFMBT1 inhibition. Conclusion: Taken together, the results of the current study highlight the ability of EZH2 to potentially inactivate the TGFβ/SMAD pathway via upregulation of miR-125a-5p-dependent SFMBT1during the progression of psoriatic lesions.